2002
DOI: 10.1046/j.1365-2311.2002.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Facultative bacterial endosymbionts benefit pea aphids Acyrthosiphon pisum under heat stress

Abstract: 1. Natural populations of pea aphids in California contain at least two facultative bacterial secondary symbionts (pea aphid secondary symbiont, PASS, or pea aphid rickettsia, PAR) in a range of frequencies throughout the state. 2. Two pea aphid clones without either of these facultative associates failed to reproduce in the first 8 days after the final moult if they had been heat‐stressed for a period of about 4 h at 39 °C as 1‐day‐old larvae in the laboratory. 3. Aphids infected artificially with PASS, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
583
1
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 641 publications
(608 citation statements)
references
References 30 publications
13
583
1
11
Order By: Relevance
“…This result is perhaps not surprising, because this isolate of S. symbiotica was found to confer only moderate resistance to wasps, and parasitism interfered with reproduction such that infected, parasitized aphids received no direct fitness benefit to infection (Oliver et al 2003(Oliver et al , 2006. Other reports indicate that S. symbiotica provides thermal protection in A. pisum (Chen et al 2000;Montllor et al 2002;Russell & Moran 2006), and this effect may explain the persistence of this inherited symbiont in aphid populations in nature.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This result is perhaps not surprising, because this isolate of S. symbiotica was found to confer only moderate resistance to wasps, and parasitism interfered with reproduction such that infected, parasitized aphids received no direct fitness benefit to infection (Oliver et al 2003(Oliver et al , 2006. Other reports indicate that S. symbiotica provides thermal protection in A. pisum (Chen et al 2000;Montllor et al 2002;Russell & Moran 2006), and this effect may explain the persistence of this inherited symbiont in aphid populations in nature.…”
Section: Discussionmentioning
confidence: 85%
“…Experimental laboratory assays have identified diverse beneficial roles conferred by inherited symbionts of invertebrates (e.g. Montllor et al 2002;Oliver et al 2003;Tsuchida et al 2004). These studies identify potential mechanisms by which symbionts may invade and persist in host populations, but do not explicitly test the population dynamics of the mutualist symbiont infections within host populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symbiotic bacteria play important roles in protecting their insect hosts from various threats, including viruses [61,62], fungal pathogens [13,15,63], parasites [64] and predators [65,66], as well as abiotic hazards such as heat shock [67,68]. However, these protective effects can differ markedly within a single symbiont 'species' [5,11,15].…”
Section: Discussionmentioning
confidence: 99%
“…Because of this interdependence, aphids are highly constrained to the ecological tolerances of Buchnera (Dunbar et al 2007). In the field, temperatures ranging from 25 to 308C result in pea aphids with lower densities of Buchnera (Montllor et al 2002). A recent study (Dunbar et al 2007) showed that heat tolerance of pea aphids and Buchnera could be destroyed with a single nucleotide deletion in a heat shock gene promoter.…”
Section: Fungus-conferred Heat Tolerance In Desert Plantsmentioning
confidence: 99%